LINGUISTIC AND ECOLOGICAL INTERPRETATIONS OF THE CONCEPT OF LANGUAGE ENVIRONMENT AND THEIR THEORETICAL FOUNDATIONS (International journal of artificial intelligence, 2026)
In this article, the linguoecological interpretations of the concept of the language environment are theoretically analyzed. Issues of the formation and stability of the ecology of the Uzbek language are highlighted based on symbolic, natural, sociocultural, and cognitive approaches.